El documento como instrumento de poder en las Reales Audiencias Indianas: el caso de Santa Fe - Jorge Pérez Cañete (Centre de Recherches sur les Mondes Américains, 2017)
After the discovery and colonization of the Americas, the need to transfer the jurisdiction of the Spanish Monarchy to the new territories led, on the one hand, to the delegation of this jurisdiction to certain institutions that were gradually established in the New World and, on the other hand, to the use of diverse tools that favored this delegation and allowed the expansion of the Atlantic Spanish Empire by mitigating the vast distance existing between these territories and the Royal authority. The aim of this paper is to analyze the use of the document as one of those tools used by the Crown to consolidate its power, focusing on the Royal Indian Audiences, institutions that were constituted as representatives of the monarch in those distant lands, and paying special attention to the reactions that these uses generated among its contemporaries.